Application of Cassava Slicing Machine Technology in Production Cassava Chips in Sari Rejo Medan - Sinamo, Karina Nola; Karo-karo, Terip; Ginting, Sentosa; Veronica, Afryna (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The process of making cassava chips carried out by partner was still simple because the process of slicing cassava which was done manually with tool made of wood and knife blade. Workers need a lot of energy, time, and concentration in order to produce uniform cassava slices and were sometimes hit by the knife of the equipment. In addition, the process of slicing cassava taked a long time so that partner was inhibited to increase the amount of production. The solutions that would be offered by the service team were the existence of science and technology which was provided in the form of (1) provision of a cassava slicing machine according to partner needs, (2) training on using a cassava slicing machine to partner, (3) training on adding seasoning variants to cassava chips, packaging, and labeling. The results obtained were partners become skilled at using a cassava slicing machine, the cassava slicing time with a machine was faster, namely 41.98 grams/second, and cassava chips were produced with flavor variants so that partner was expected to be assisted in the process of cassava chips production and partner businesses can develop.